Mechanical Properties of Lining Leathers Finished with the Addition of Oregano Essential Oil - Bielak, Elżbieta; Marcinkowska, Ewa (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The hygienic properties of lining leathers can be improved significantly by introducing oregano essential oil into leathers. This is because adding antiseptic oil makes leathers more resistant to microorganisms that are potentially harmful to humans and cause damage to animal leathers. The paper presents the results of tests to check selected mechanical properties – tensile strength, elongation and tear load – of leathers fatliquored with oregano essential oil at a concentration of 3% w/w and without this treatment. The tests were carried out on the Instron 5544 testing machine. The leathers enriched with oil met the standard requirements set for lining leathers for of the parameters: tensile strength and elongation. Statistical analysis using the chi-squared, Hartley and Fisher-Snedecor tests at an assumed significance level of α = 0.05 revealed that leather enriched with oregano essential oil has a significantly higher tensile strength than leather fatliquored without this oil, while both leather samples showed no significant difference in elongation and tear load. Thus, it can be concluded that adding 3% w/w of oil will have not have an adverse effect on basic mechanical properties of leathers.